Understanding the Endocrine and Molecular Signaling Cascade Regulation Pathways in Children with Hypospadias - Bangalore, Raghunath V; Asthana, Suramya; R., Reshma V.; Saini, Deepak Kumar; Alladi, Anand (Journal of Pediatric Genetics, 2024)
Hypospadias (HS) is a congenital defect that occurs due to defective androgenization. It is characterized by the aberrant location of the urinary meatus on the ventral aspect of the penis with various degrees of severity. The molecular mechanisms and genetic associations underlying the condition remain largely unknown. Existing literature revolves around surgical and medical management of the condition. Human chorionic gonadotropin pretreatment in HS is proposed to decrease the severity of the anomaly and improve the clinical outcome of surgery. The underlying mechanisms that drive these outcomes have not been explored. Few studies have explored the endocrine signaling and pathways which lead to the development of the condition. Hence, a prospective study was conducted to understand the same. Eighteen children with mid or proximal penile HS were included as cases, and nine children undergoing circumcision for phimosis (nonpathological) were included as controls. Serum samples from all these children and preputial skin samples taken during surgery were used in the analysis. The hormonal milieu was normal in all children in our cohort. A comparison of previously reported genes with our cohort sequencing revealed changes in several major pathways involved in cell proliferation and differentiation, cell signaling, angiogenesis, and immune response pathways. Compared with healthy controls, HS subjects had 152 differentially expressed genes. Of these, 93 genes were up-regulated, and 59 genes were found to be significantly down-regulated. The gene expression evaluation also showed changes in expression patterns in inflammatory genes and link RNAs, unlike previously reported genes.
Keywords: hypospadias; genetics; molecular signaling; testosterone; di-hydro testosterone